PREDIKTOR SYMPTOMATIC INTRACEREBRAL HEMORRHAGE PASCATROMBOLISIS INTRAVENA PADA STROKE ISKEMIK AKUT - Al Rasyid; Salim Harris; Mohammad Kurniawan; Rakhmad Hidayat; Taufik Mesiano (NEURONA, 2018)
PREDICTORS OF SYMPTOMATIC INTRACEREBRAL HEMORRHAGE FOLLOWING INTRAVENOUS THROMBOLYSIS IN ACUTE ISCHEMIC STROKEABSTRACTDespite its effectiveness, the percentage of ischemic stroke patients who received definitive treatment, thrombolysis, never went above 10%, due to one of the reason is the occurrence of severe, post-therapeutic complications, such as symptomatic intracerebral hemorrhage (sICH). Several factors contribute to sICH occurrence are age, severity of stroke, early changes of ischemic sign, hyperglycemia, blood pressure, antiplatelet use and its interval. Patients with highest risk of sICH has been shown to have the greatest benefits from thrombolysis among other subgroup patients, therefore withholding therapy is not a choice. Compliance to the stroke’s guidelines could reduce the risk of complications as well as boost effectiveness of treatment.Keywords: Safety predictors, acute ischemic stroke, thrombolysis, sICH ABSTRAK Walau terbukti efektif, persentase pasien yang dapat dilakukan tindakan definitif stroke iskemik akut berupa trombolisis  tidak  pernah  mencapai  angka  10%,  salah  satunya  disebabkan  pertimbangan  terhadap  komplikasi  berat, seperti symptomatic intracerebral hemorrhage (sICH). Beberapa faktor yang berpengaruh terhadap kejadian sICH antara lain usia, derajat stroke, perubahan tanda iskemik dini, hiperglikemia dan diabetes melitus, tekanan darah, penggunaan antiplatelet, serta waktu pemberian. Pasien dengan risiko sICH tertinggi memiliki keuntungan terbesar dari trombolisis sehingga menunda tindakan bukanlah suatu opsi. Kepatuhan terhadap panduan tindakan dapat mengurangi angka kejadian komplikasi berat.Kata kunci: Prediktor keamanan, stroke iskemik akut, trombolisis, sICH